Sedimentation Velocity Analytical Ultracentrifugation of Oxidized Recombinant Full-Length Factor VIII - Zakas, Philip M.; Healey, John F.; Smith, Ian W.; Lillicrap, David; Lollar, Pete (Frontiers in Immunology, 2020)
Anti-drug antibodies to coagulation factor VIII (fVIII), often termed inhibitors, present the greatest economical and treatment related obstacle in the management of hemophilia A. Although several genetic and environmental risk factors associated with inhibitor development have been identified, the precise mechanisms responsible for the immune response to exogenous fVIII therapies remain undefined. Clinical trials suggest there is an increased immunogenic potential of recombinant fVIII compared to plasma-derived products. Additional biochemical and immunological studies have demonstrated that changes in recombinant fVIII production and formulation can alter fVIII structure and immunogenicity. Recently, one study demonstrated increased immunogenicity of the recombinant fVIII product Helixate in hemophilia A mice following oxidation with hypochlorite (ClO-). It is widely reported that protein aggregates within drug products can induce adverse immune reactions in patients. Several studies have therefore investigated the prevalence of molecular aggregates in commercial recombinant products with and without use-relevant stress and agitation. To investigate the potential link between oxidation-induced immunogenicity and molecular aggregation, we analyzed the recombinant fVIII product, Helixate, via sedimentation velocity analytical ultracentrifugation following oxidation with ClO-. At 80 µM ClO-, a concentration that reduced the specific-activity by 67%, no detectable increase in large molecular aggregates (s > 12 S) was observed when compared to non-oxidized fVIII. This lack of aggregates was demonstrated both in commercial excipient as well as a HEPES buffered saline formulation. These data suggest that oxidation induced immunogenicity is independent of aggregate-mediated immune response. Therefore, our data support multiple, independent mechanisms underlying fVIII immunogenicity.